Polszczyzna urzędowa i jej warianty - Malinowska, Ewa (Stylistyka, 2021)
The aim of this paper is to make an attempt to determine the status of language in the ad- ministrative-legal language communication sphere and a proposal for an intemal diffe- rentiation of this variety of Polish. The author supports the tradition of using the name administrative variant as the one of higher order to all the expressions servicing this sphere, and to distinguish within its scope the following: the legał subvariant as the central one (law is the broadest framework of administrative activities), the office subvariant and the rhetoric subvariant. Each of them may have a further differentiation depending on the assumed criteria.